FIRST RECORD OF CANTHARELLUS MINOR IN VIETNAM - Phan, Hung Huu; Lao, Thuan Duc; Ai Le, Thuy Huyen; Hoang, Khanh Quoc; Truong, Nguyen Binh; Lam Ngo, Giang Thi (Vietnam Journal of Biotechnology, 2018)
This species of mushroom with orange fruiting bodies and yellow flesh grows in clumps on the forest land in the coordinates 11o56'34.45" N, 108o28'33.56" E in the pine (Pinus kesiya) forest, Da Lat City, Lam Dong Province, Vietnam. The results of analysis on the morphology, both macro- and micro-morphological characteristics of this mushroom showed that, pileus: 5-15 mm wide, infundibuliform; yellowish to orange; margin incurred, wavy-liked margin, non-striate; Pileus surface: smooth, scaleless, yellowish; Lamellae: distant, decurrent, not intervenose, concolorous to pileus; Context: concolourous to the pileus, slight sweetness, aromatic flavor; Stipe: cylindrical shape, surface smooth, concolourous to pileus, 1-2 mm diameter, 20-50 mm length; Basidiospores: 6-11.5 x 4-6.5 μm, ovoid-ellipsoid with smooth surface; Basidia: 65 x 10 μm, cornuted 4-6 spores per basidium. Phylogenetic analysis of nrLSU sequence yielded consistent topology in different taxa of Cantharellus. The phylogenetic position of XC02 was obtained and accepted at sub-generic level: subgenus Parvocantharellus. This clade was suggested to be monophyletic, and separated from other sub-generic levels. Morphologically phylogenetically distinct from the other species of clade 4, such as C. appalachiensis, C. tabernensis, C. aff. Congolensis. The highly supported monophyletic group with referent Cantharellus minor was obtained with the bootstrap value of 99, indicated that XC02 was significant closely to Cantharellus minor. Phylogenetic of nrLSU analysis revealed clades with statistical support corresponding to morphological observation, thus, XC2 was concluded as Cantharellus minor.